MODEL PERILAKU MAHASISWA PENGGUNA MOBIL KE KAMPUS BERDASARKAN THEORY OF PLANNED BEHAVIOR - Setiawan, Rudy; Santosa, Wimpy; Sjafruddin, Ade (Jurnal Transportasi, 2013)
The most common daily trip for students is the commute to and from campus. Though there are clear environmental, economic, and social drawback from using private vehicles for these trips, students still choose private vehicles to get to campus. This study reports an investigation of psychological factors influencing studentsâ behavior to commute by car from the perspective of the Theory of Planned Behavior (TPB). Students from three different university campuses (sample size of 312) completed a survey on their car commuting behavior. Results indicated that all relations postulated by the TPB are confirmed and perceived behavioral control was the strongest factor that influences studentsâ intention. Attitude, subjective norm, and perceived behavioral control explain 59% variance of the intention while intention explains 58% of the variance of the actual car use. Implications of these findings are that in order to alter the use of car, interventions should target the perceived behavioral control of commuting by car.